2013
DOI: 10.2196/jmir.2708
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media on Medical Professionalism: A Systematic Qualitative Review of Challenges and Opportunities

Abstract: BackgroundThe rising impact of social media on the private and working lives of health care professionals has made researchers and health care institutions study and rethink the concept and content of medical professionalism in the digital age. In the last decade, several specific policies, original research studies, and comments have been published on the responsible use of social media by health care professionals. However, there is no systematic literature review that analyzes the full spectrum of (1) socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(91 citation statements)
references
References 39 publications
2
84
0
5
Order By: Relevance
“…A plethora of research has convincingly shown that use of social media supplements delivery and understanding of medical education [14], lifelong learning [15], and medical professionalism [16]. The use of social media in medical education for active learning demands incorporation of scientifically designed program that should address ethics [17], facilitate group learning [18] especially at the workplace-based education [19] in an interprofessional environment [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of research has convincingly shown that use of social media supplements delivery and understanding of medical education [14], lifelong learning [15], and medical professionalism [16]. The use of social media in medical education for active learning demands incorporation of scientifically designed program that should address ethics [17], facilitate group learning [18] especially at the workplace-based education [19] in an interprofessional environment [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature discusses that while those born after 1980 are somewhat "native" to the digital age, people born before 1980 are still somewhat considered immigrants to the digital age [20] due to the difficulty adopting to the intricacies of the social media. The authors state that these differences may soon be gone, and further distinctions may arise among the natives.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is little information about trends in qualitative and mixed methods approaches to social media research. Prior literature reviews have included discussions of trends in research approaches but have provided a more global classification of general trends (e.g., Best et al, Gholami-Kordkheili, Wild, and Strech (2013) Research, commentaries, editorials, and opinion papers on medical professionalism and social media Health care and medical 108 Hamm et al (2013) Research on social media use by health-care professionals or trainees published between 2000 and 2012…”
mentioning
confidence: 99%